(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The most shocking incident in the history of Indian peninsula was that the country was divided into two separate nations (i.e. India and Pakistan) at the end of the colonial era. The partition that was based on religious identity had created unprecedented tensions among the Indians resulted in devastating communal riots. Human rights were badly violated by the fanatics and their heinous acts of bigotry. Although women were hardly given any opportunity to be the part of freedom fighting, they became the worst victim of partition violence. Bapsi Sidhwa’s Ice-Candy Man which is one of the most remarkable works based on Indian partition provides us with a sincere representation of the terrible impact of it on people of the subcontinent especially on the women. It gives a pictorial account of exploitation, rape, murder, abduction, assault on the private parts of the women, and amputation of their breasts that happened to be very common during the time of partition. In the present novel, Sidhwa has drawn an imaginary connection between a female body and territorial landmass of the undivided India. Here, the character Ayah is a metaphorical figure representing nation as a woman or a mother. The molestation of Ayah’s body can be equated with the molestation (partition) of India. The present paper will foreground the dimensions in which gender relation is essential in understanding and analyzing the phenomena of nation. It will take up feminist approach to show oppression and exploitation against women as portrayed in the novel to drive home the conclusion, and will suggest possible ways for the emancipation of the women.